Стандартизація в музиці - Захарова, Е. О. (ХНУРЕ, 2024)
The history of choosing the musical scale reference point is considered. The issues of standardization of scale frequencies are investigated. The history of the construction of a universal scale is described. The methodology for constructing a 12-step uniformly tempered scale is outlined. The standardization of musical scale frequencies has been studied. Different types of musical scales are compared.
Keywords: стандартизація в музиці